2021
DOI: 10.3390/polym13071162
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research Progress on Lignin-Derived Resins for Natural Fiber Composite Applications

Abstract: By increasing the environmental concerns and depletion of petroleum resources, bio-based resins have gained interest. Recently, lignin, vanillin (4-hydroxy-3-methoxybenzaldehyde), and divanillin (6,6′-dihydroxy-5,5′-dimethoxybiphenyl-3,3′-dicarbaldehyde)-based resins have attracted attention due to the low cost, environmental benefits, good thermal stability, excellent mechanical properties, and suitability for high-performance natural fiber composite applications. This review highlights the recent use of lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 173 publications
(271 reference statements)
1
25
0
Order By: Relevance
“…Small volume and niche applications are verified in usage of nontoxic technical lignins, e.g., in feed pellet production and as UV absorber, as activated carbon, and as replacement for carbon black (Puls, 2009;Higson and Smith, 2021). Although little has yet been implicated on an industrial scale, research on lignins revealed a huge potential for valorization in applications to serve as fillers, reinforcing agents, adhesives, emulsifiers, and dispersants, as well as feedstock of low cost and specialty chemicals, gels, nanoparticles, absorbers, flocculants, composites, biofoams, bioplastics, sensors and electrodes, and other novel biomaterials (Upton and Kask, 2015;Kai et al, 2016;Collins et al, 2019;Yang et al, 2019;Zhang et al, 2019;Jiang et al, 2020;Moreno and Sipponen, 2020;Wang et al, 2020;Yu and Kim, 2020;Aristri et al, 2021;Karthäuser et al, 2021;Kumar et al, 2021;Liu et al, 2021;Ma et al, 2021;Melro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small volume and niche applications are verified in usage of nontoxic technical lignins, e.g., in feed pellet production and as UV absorber, as activated carbon, and as replacement for carbon black (Puls, 2009;Higson and Smith, 2021). Although little has yet been implicated on an industrial scale, research on lignins revealed a huge potential for valorization in applications to serve as fillers, reinforcing agents, adhesives, emulsifiers, and dispersants, as well as feedstock of low cost and specialty chemicals, gels, nanoparticles, absorbers, flocculants, composites, biofoams, bioplastics, sensors and electrodes, and other novel biomaterials (Upton and Kask, 2015;Kai et al, 2016;Collins et al, 2019;Yang et al, 2019;Zhang et al, 2019;Jiang et al, 2020;Moreno and Sipponen, 2020;Wang et al, 2020;Yu and Kim, 2020;Aristri et al, 2021;Karthäuser et al, 2021;Kumar et al, 2021;Liu et al, 2021;Ma et al, 2021;Melro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because they are available in large quantities, lignosulfonates and kraft lignin are most interesting polyphenols for the development of binders for wood composites. Due to the high content of phenolic groups, both technical lignins are considered to be very suitable green substitutes in existing binder systems (Mansouri et al, 2007;Tejado et al, 2007;Norström et al, 2018;Jiang et al, 2020;Wang et al, 2020;Aristri et al, 2021;Karthäuser et al, 2021;Kumar et al, 2021;Ostendorf et al, 2021). Nonetheless, extensive research is required before a successful industrial implication.…”
Section: Introductionmentioning
confidence: 99%
“…Netkueakul et al, studied the effect of DOPO and graphene nanoplatelets (GNP) in flame retardant epoxy resin (EP), and found the peak heat release rate of EP was dramatically decreased with an increase in the DOPO content, while the smoke production of EP/DOPO/GNP composites was suppressed in comparison with EP containing only DOPO as flame retardant 14 . Many phosphorus‐nitrogen compounds facilitate the formation of protective char as effective barrier to prevent the transfer of heat and volatiles, and thus they have high efficiency in EP flame retardation 15,16 . Shi et al 17 synthesized a melamine phenylphosphate (MPhP) and found that the limiting oxygen index (LOI) of EP with 20 wt% MPhP incorporation was elevated from 20.5% to 26.5% with V0 rate achieved in UL‐94 standard.…”
Section: Introductionmentioning
confidence: 99%
“…EU‐based epoxy resins have been produced limitedly after lignin and vanillin‐based resins 9–12 . Owing to their low flammability, high‐thermal stability, and high‐fracture toughness, they are attractive for electronics, coatings, fiber composites, adhesives, and flame protection applications 13–16 .…”
Section: Introductionmentioning
confidence: 99%